2022
DOI: 10.3390/medicina58050637
|View full text |Cite
|
Sign up to set email alerts
|

Management of Hypertension with Female Sexual Dysfunction

Abstract: Female sexual dysfunction (FSD) in hypertension has been less studied than male sexual dysfunction, and antihypertensive agents’ impact on female sexual function is not defined. In this review, randomized double-blind clinical trials and cross-sectional studies related to female sexual function in hypertension were analyzed from 1991 to 2021. FSD appeared to be higher in hypertensive women than in normotensive women. Beta-blockers are the only antihypertensive agents with relatively strong evidence of damaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…The main symptoms of female sexual dysfunction include pain during sexual intercourse or unpleasurable sex, lack of orgasm, low sexual desire, lack of arousal or decreased libido, and difficulty with vaginal lubrication. 16 , 24 , 27 Moreover, although it has been established that hypertension is associated with sexual dysfunction in men, this phenomenon has been poorly studied in women. However, the few available studies indicate that women with hypertension also experience sexual dysfunction, affecting all domains, such as sexual desire, arousal, lubrication, orgasm, satisfaction, and pain.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The main symptoms of female sexual dysfunction include pain during sexual intercourse or unpleasurable sex, lack of orgasm, low sexual desire, lack of arousal or decreased libido, and difficulty with vaginal lubrication. 16 , 24 , 27 Moreover, although it has been established that hypertension is associated with sexual dysfunction in men, this phenomenon has been poorly studied in women. However, the few available studies indicate that women with hypertension also experience sexual dysfunction, affecting all domains, such as sexual desire, arousal, lubrication, orgasm, satisfaction, and pain.…”
Section: Resultsmentioning
confidence: 99%
“…High blood pressure can worsen fibrosis in female genital tissue and cause damage to endothelial cells due to oxidation and inflammation related to hypertension. 11 , 27 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, some, 12 but not all, 13 studies have suggested that FSD improves with antihypertensive treatment. In contrast, however, beta‐blockers have been shown to worsen sexual function in women 14 …”
Section: Introductionmentioning
confidence: 99%
“…In contrast, however, beta-blockers have been shown to worsen sexual function in women. 14 Only a few studies have examined the relationship between atherosclerosis and FSD. Atherosclerosis is a lipid-driven chronic inflammatory process that leads to plaque build-up inside arteries, reducing arterial blood flow.…”
Section: Introductionmentioning
confidence: 99%